Participation of urban markets in development in Africa - (:unkn) unknown (My University, 2022)
Urban markets being a vector of distribution and consumption influence all sectors of the urban economy, which allows them to influence the development of cities in Africa. Thus, this article, which is a theoretical study, aims to analyze the contribution of markets to the development of African cities. This research reveals that urban markets in Africa allow people to have regular income and access to the products necessary for urban life. However, these markets very often have a negative influence on the environment (through the waste produced there), the economy (through its informal nature) and socially (through the quality of the products sold there). Thus, many challenges remain to be met for a better contribution of markets to urban development in Africa.
Keywords: African Research